The Influence of Work Interest and Lifestyle on Non-Office Career Choices with Career Self-Efficacy as a Mediating Variable: Evidence from Generation Z Students - Fadilah , Dimas Rizki; Fadli , Uus Mohammad Darul Fadli; Rosmawati , Ery Rosmawati (Research in Management of Technology and Business, 2026)
This study aims to examine how career interests and lifestyles influence career decisions outside the office, with career efficacy acting as a mediating variable among Generation Z students. The development of digital technology has opened up various technology-based job opportunities that offer flexibility, such as freelance work, content creation, and entrepreneurship, thus increasing interest in non-office career paths. This study employed a quantitative approach with an explanatory survey method, which was completed by 214 students from the 2022 intake of the Management programme at the University of Buana Perjuangan Karawang. Data analysis was performed using Covariance-Based Structural Equation Modelling (CB-SEM) with SmartPLS 4 software. The results of the study showed that career self-efficacy had a positive and significant influence on non-office career choices, while work interest and lifestyle also had a significant influence on non-office career choices, both directly and indirectly through career self-efficacy. These findings emphasise that students' belief in their career capabilities is a key factor in shaping non-traditional career decisions in the digital era.